Identification and Biotyping of Pythium insidiosum Isolated from Urban and Rural Areas of Thailand by Multiplex PCR, DNA Barcode, and Proteomic Analyses - Zin Mar Htun; Aree Laikul; Watcharapol Pathomsakulwong; Chompoonek Yurayart; Tassanee Lohnoo; Wanta Yingyong; Yothin Kumsang; Penpan Payattikul; Pattarana Sae-Chew; Thidarat Rujirawat; Paisan Jittorntam; Chalisa Jaturapaktrarak; et al. (Journal of Fungi, 2021)
Pythium insidiosum causes pythiosis, a fatal infectious disease of humans and animals worldwide. Prompt diagnosis and treatment are essential to improve the clinical outcome of pythiosis. Diagnosis of P. insidiosum relies on immunological, molecular, and proteomic assays. The main treatment of pythiosis aims to surgically remove all affected tissue to prevent recurrent infection. Due to the marked increase in case reports, pythiosis has become a public health concern. Thailand is an endemic area of human pythiosis. To obtain a complete picture of how the pathogen circulates in the environment, we surveyed the presence of P. insidiosum in urban (Bangkok) and rural areas of Thailand. We employed the hair-baiting technique to screen for P. insidiosum in 500 water samples. Twenty-seven culture-positive samples were identified as P. insidiosum by multiplex PCR, multi-DNA barcode (rDNA, cox1, cox2), and mass spectrometric analyses. These environmental strains of P. insidiosum fell into Clade-II and -III genotypes and exhibited a close phylogenetic/proteomic relationship with Thai clinical strains. Biodiversity of the environmental strains also existed in a local habitat. In conclusion, P. insidiosum is widespread in Thailand. A better understanding of the ecological niche of P. insidiosum could lead to the effective prevention and control of this pathogen.